Pengembangan Potensi Desa Melalui Pelatihan Sistem Administrasi Dengan Microsoft Excel Pada Desa Bojonggede - Prambodo, Yoga Listi; Bani, Alexius Ulan; Nugroho, Fifto; Kurnia, Mega Tri (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2022)
The administrative system is very important in the world of trade and transactions, because with a good administrative system, business owners can know and control the flow of goods circulation and people around public services. Therefore, it is necessary to develop village potential trough out Microsoft Office Excel training so the community will be developed and increased the productivity of the potential in the village. Microsoft Excel is a program issued by Microsoft Office with a function as a numerical data processing program. Various kinds of data processing activities, making graphs, calculating data and others can be used in Microsoft Excel. Thus, training related to Microsoft Excel is carried out and it is hoped that this knowledge can improve abilities and support the potential that exists in Bojonggede village.